Artificial Diiron Enzymes with a De Novo Designed Four‐Helix Bundle Structure (Eur. J. Inorg. Chem. 21/2015). Issue 21 (28th July 2015) - Chino, Marco; Maglio, Ornella; Nastri, Flavia; Pavone, Vincenzo; DeGrado, William F.; Lombardi, Angela
Abstract : The front cover picture shows a construction site where workers are building up a four‐helix bundle scaffold. A protein designer, working like an architect, has to adjust each minimal structural element in order to build up a stable and functional model. The metal site in the helical bundle scaffold represents the heart of the construction. Fine‐tuning of the metal binding site enables a specific function, such as oxidative chemistry. This approach has been successfully employed to develop diiron–oxo protein models. Details are presented in the Microreview by A. Lombardi et al. onp. 3371 ff . For more on the story behind the cover research, see theCover Profile .